Bioluminescence dynamics in single germinating bacterial spores reveal metabolic heterogeneity - Frentz, Zak (J R Soc Interface, 2020)
Spore-forming bacteria modulate their metabolic rate by over five orders of magnitude as they transition between dormant spores and vegetative cells and thus represent an extreme case of phenotypic variation. During environmental changes in nutrient availability, clonal populations of spore-forming bacteria exhibit individual differences in cell fate, the timing of phenotypic transitions and gene expression. One potential source of this variability is metabolic heterogeneity, but this has not yet been measured, as existing single-cell methods are not easily applicable to spores due to their small size and strong autofluorescence. Here, we use the bacterial bioluminescence system and a highly sensitive microscope to measure metabolic dynamics in thousands of B. subtilis spores as they germinate. We observe and quantitate large variations in the bioluminescence dynamics across individual spores that can be decomposed into contributions from variability in germination timing, the amount of endogenously produced luminescence substrate and the intracellular reducing power. This work shows that quantitative measurement of spore metabolism is possible and thus it opens avenues for future study of the thermodynamic nature of dormant states.